Shallow Water DG Simulations on FPGAs: Design and Comparison of a Novel Code Generation Pipeline - Alt, Christoph; Kenter, Tobias; Faghih-Naini, Sara; Faj, Jennifer; Opdenhövel, Jan-Oliver; Plessl, Christian; Aizinger, Vadym; Hönig, Jan; Köstler, Harald (Lecture Notes in Computer Science)

Probabilistic Scoring Lists for Interpretable Machine Learning - Hanselle, Jonas Manuel; Fürnkranz, Johannes; Hüllermeier, Eyke (26th International Conference on Discovery Science)

iSAGE: An Incremental Version of SAGE for Online Explanation on Data Streams - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Machine Learning and Knowledge Discovery in Databases: Research Track)

Deciding Subsumption in Defeasible $$\mathcal {ELI}_\bot $$ with Typicality Models - de Camargo e Souza Câmara, Igor; Turhan, Anni-Yasmin (Logics in Artificial Intelligence)

Neural Class Expression Synthesis in ALCHIQ(D) - Kouagou, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Machine Learning and Knowledge Discovery in Databases: Research Track)
Class expression learning in description logics has long been regarded as an iterative search problem in an infinite conceptual space. Each iteration of the search process invokes a reasoner and a heuristic function. The reasoner finds the instances of the current expression, and the heuristic function computes the information gain and decides on the next step to be taken. As the size of the background knowledge base grows, search-based approaches for class expression learning become prohibitively slow. Current neural class expression synthesis (NCES) approaches investigate the use of neural networks for class expression learning in the attributive language with complement (ALC). While they show significant improvements over search-based approaches in runtime and quality of the computed solutions, they rely on the availability of pretrained embeddings for the input knowledge base. Moreover, they are not applicable to ontologies in more expressive description logics. In this paper, we propose a novel NCES approach which extends the state of the art to the description logic ALCHIQ(D). Our extension, dubbed NCES2, comes with an improved training data generator and does not require pretrained embeddings for the input knowledge base as both the embedding model and the class expression synthesizer are trained jointly. Empirical results on benchmark datasets suggest that our approach inherits the scalability capability of current NCES instances with the additional advantage that it supports more complex learning problems. NCES2 achieves the highest performance overall when compared to search-based approaches and to its predecessor NCES. We provide our source code, datasets, and pretrained models at https://github.com/dice-group/NCES2.

Integrating Safety Guarantees into the Learning Classifier System XCS - Hansmeier, Tim; Platzner, Marco (Applications of Evolutionary Computation, EvoApplications 2022, Proceedings)

Overview of Touché 2022: Argument Retrieval - Bondarenko, Alexander; Fröbe, Maik; Kiesel, Johannes; Syed, Shahbaz; Gurcke, Timon; Beloucif, Meriem; Panchenko, Alexander; Biemann, Chris; Stein, Benno; Wachsmuth, Henning; Potthast, Martin; Hagen, Matthias (Lecture Notes in Computer Science)

Towards Situational Process Management for Professional Education Programmes - Wolters, Dennis; Engels, Gregor (Product-Focused Software Process Improvement)

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Approximation and Online Algorithms)

Development of a Hybrid Modeling Methodology for Oscillating Systems with Friction - Wohlleben, Meike Claudia; Bender, Amelie; Peitz, Sebastian; Sextro, Walter (Machine Learning, Optimization, and Data Science)

Tab2Onto: Unsupervised Semantification with Knowledge Graph Embeddings - Zahera, Hamada Mohamed Abdelsamee; Heindorf, Stefan; Balke, Stefan; Haupt, Jonas; Voigt, Martin; Walter, Carolin; Witter, Fabian; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2022 Satellite Events)

MultPAX: Keyphrase Extraction Using Language Models and Knowledge Graphs - Zahera, H.M.A; Vollmers, Daniel; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (The Semantic Web – ISWC 2022)

Learning Concept Lengths Accelerates Concept Learning in ALC - KOUAGOU, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (The Semantic Web)

Drift Detection in Text Data with Document Embeddings - Feldhans, Robert; Wilke, Adrian; Heindorf, Stefan; Shaker, Mohammad Hossein; Hammer, Barbara; Ngonga Ngomo, Axel-Cyrille; Hüllermeier, Eyke (Intelligent Data Engineering and Automated Learning – IDEAL 2021)

An OCR Pipeline and Semantic Text Analysis for Comics - Hartel, Rita; Dunst, Alexander (MANPU 2020: The 4th International Workshop on coMics ANalysis, Processing and Understanding@Pattern Recognition. ICPR International Workshops and Challenges)

Efficient Adaptively-Secure IB-KEMs and VRFs via Near-Collision Resistance - Jager, Tibor; Kurek, Rafael; Niehues, David (Public-Key Cryptography – PKC 2021)
We construct more efficient cryptosystems with provable security against adaptive attacks, based on simple and natural hardness assumptions in the standard model. Concretely, we describe: – An adaptively-secure variant of the efficient, selectively-secure LWE- based identity-based encryption (IBE) scheme of Agrawal, Boneh, and Boyen (EUROCRYPT 2010). In comparison to the previously most efficient such scheme by Yamada (CRYPTO 2017) we achieve smaller lattice parameters and shorter public keys of size O(log λ), where λ is the security parameter. – Adaptively-secure variants of two efficient selectively-secure pairing- based IBEs of Boneh and Boyen (EUROCRYPT 2004). One is based on the DBDH assumption, has the same ciphertext size as the cor- responding BB04 scheme, and achieves full adaptive security with public parameters of size only O(log λ). The other is based on a q- type assumption and has public key size O(λ), but a ciphertext is only a single group element and the security reduction is quadrat- ically tighter than the corresponding scheme by Jager and Kurek (ASIACRYPT 2018). – A very efficient adaptively-secure verifiable random function where proofs, public keys, and secret keys have size O(log λ). As a technical contribution we introduce blockwise partitioning, which leverages the assumption that a cryptographic hash function is weak near-collision resistant to prove full adaptive security of cryptosystems.

Verifiable Random Functions with Optimal Tightness - Niehues, David (Public-Key Cryptography – PKC 2021)
Verifiable random functions (VRFs), introduced by Micali, Rabin and Vadhan (FOCS’99), are the public-key equivalent of pseudo- random functions. A public verification key and proofs accompanying the output enable all parties to verify the correctness of the output. How- ever, all known standard model VRFs have a reduction loss that is much worse than what one would expect from known optimal constructions of closely related primitives like unique signatures. We show that: 1. Every security proof for a VRF that relies on a non-interactive assumption has to lose a factor of Q, where Q is the number of adver- sarial queries. To that end, we extend the meta-reduction technique of Bader et al. (EUROCRYPT’16) to also cover VRFs. 2. This raises the question: Is this bound optimal? We answer this ques- tion in the affirmative by presenting the first VRF with a reduction from the non-interactive qDBDHI assumption to the security of VRF that achieves this optimal loss. We thus paint a complete picture of the achievability of tight verifiable random functions: We show that a security loss of Q is unavoidable and present the first construction that achieves this bound.

Ranking Structured Objects with Graph Neural Networks - Damke, Clemens; Hüllermeier, Eyke (Proceedings of The 24th International Conference on Discovery Science (DS 2021))
Graph neural networks (GNNs) have been successfully applied in many structured data domains, with applications ranging from molecular property prediction to the analysis of social networks. Motivated by the broad applicability of GNNs, we propose the family of so-called RankGNNs, a combination of neural Learning to Rank (LtR) methods and GNNs. RankGNNs are trained with a set of pair-wise preferences between graphs, suggesting that one of them is preferred over the other. One practical application of this problem is drug screening, where an expert wants to find the most promising molecules in a large collection of drug candidates. We empirically demonstrate that our proposed pair-wise RankGNN approach either significantly outperforms or at least matches the ranking performance of the naive point-wise baseline approach, in which the LtR problem is solved via GNN-based graph regression.
Keywords: Graph-structured data; Graph neural networks; Preference learning; Learning to rank

Beep-And-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Algorithms for Sensor Systems (ALGOSENSORS '21))

Issuer-Hiding Attribute-Based Credentials - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Ramacher, Sebastian; Samelin, Kai (Cryptology and Network Security)

Designing a Risk Assessment Tool for Artificial Intelligence Systems - Nagbøl, Per Rådberg; Müller, Oliver; Krancher, Oliver (The Next Wave of Sociotechnical Design)

Drift Detection in Text Data with Document Embeddings - Feldhans, Robert; Wilke, Adrian; Heindorf, Stefan; Shaker, Mohammad Hossein; Hammer, Barbara; Ngonga Ngomo, Axel-Cyrille; Hüllermeier, Eyke (Intelligent Data Engineering and Automated Learning – IDEAL 2021)

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

HighPerMeshes – A Domain-Specific Language for Numerical Algorithms on Unstructured Grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz-Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Euro-Par 2020: Parallel Processing Workshops)
Solving partial differential equations on unstructured grids is a cornerstone of engineering and scientific computing. Nowadays, heterogeneous parallel platforms with CPUs, GPUs, and FPGAs enable energy-efficient and computationally demanding simulations. We developed the HighPerMeshes C++-embedded Domain-Specific Language (DSL) for bridging the abstraction gap between the mathematical and algorithmic formulation of mesh-based algorithms for PDE problems on the one hand and an increasing number of heterogeneous platforms with their different parallel programming and runtime models on the other hand. Thus, the HighPerMeshes DSL aims at higher productivity in the code development process for multiple target platforms. We introduce the concepts as well as the basic structure of the HighPerMeshes DSL, and demonstrate its usage with three examples, a Poisson and monodomain problem, respectively, solved by the continuous finite element method, and the discontinuous Galerkin method for Maxwell’s equation. The mapping of the abstract algorithmic description onto parallel hardware, including distributed memory compute clusters, is presented. Finally, the achievable performance and scalability are demonstrated for a typical example problem on a multi-core CPU cluster.
Keywords: tet_topic_hpc

Evaluating the Design Space for Offloading 3D FFT Calculations to an FPGA for High-Performance Computing - Ramaswami, Arjun; Kenter, Tobias; Kühne, Thomas; Plessl, Christian (Applied Reconfigurable Computing. Architectures, Tools, and Applications)

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Learning Choice Functions via Pareto-Embeddings - Pfannschmidt, Karlson; Hüllermeier, Eyke (Lecture Notes in Computer Science)

Hyper-parameterized Dialectic Search for Non-linear Box-Constrained Optimization with Heterogenous Variable Types - Sellmann, Meinolf; Tierney, Kevin (Lecture Notes in Computer Science)
Keywords: pc2-ressources

On the Real-World Instantiability of Admissible Hash Functions and Efficient Verifiable Random Functions - Jager, Tibor; Niehues, David (Lecture Notes in Computer Science)
Verifiable random functions (VRFs) are essentially digital signatures with additional properties, namely verifiable uniqueness and pseudorandomness, which make VRFs a useful tool, e.g., to prevent enumeration in DNSSEC Authenticated Denial of Existence and the CONIKS key management system, or in the random committee selection of the Algorand blockchain. Most standard-model VRFs rely on admissible hash functions (AHFs) to achieve security against adaptive attacks in the standard model. Known AHF constructions are based on error-correcting codes, which yield asymptotically efficient constructions. However, previous works do not clarify how the code should be instantiated concretely in the real world. The rate and the minimal distance of the selected code have significant impact on the efficiency of the resulting cryptosystem, therefore it is unclear if and how the aforementioned constructions can be used in practice. First, we explain inherent limitations of code-based AHFs. Concretely, we assume that even if we were given codes that achieve the well-known Gilbert-Varshamov or McEliece-Rodemich-Rumsey-Welch bounds, existing AHF-based constructions of verifiable random functions (VRFs) can only be instantiated quite inefficiently. Then we introduce and construct computational AHFs (cAHFs). While classical AHFs are information-theoretic, and therefore work even in presence of computationally unbounded adversaries, cAHFs provide only security against computationally bounded adversaries. However, we show that cAHFs can be instantiated significantly more efficiently. Finally, we use our cAHF to construct the currently most efficient verifiable random function with full adaptive security in the standard model.
Keywords: Admissible hash functions; Verifiable random functions; Error-correcting codes; Provable security

Modeling and Analyzing Architectural Diversity of Open Platforms - Jazayeri, Bahar; Schwichtenberg, Simon; Küster, Jochen; Zimmermann, Olaf; Engels, Gregor (Advanced Information Systems Engineering)

Using Abstract Contracts for Verifying Evolving Features and Their Interactions - Knüppel, Alexander; Krüger, Stefan; Thüm, Thomas; Bubel, Richard; Krieter, Sebastian; Bodden, Eric; Schaefer, Ina (Lecture Notes in Computer Science)
Today, software systems are rarely developed monolithically, but may be composed of numerous individually developed features. Their modularization facilitates independent development and verification. While feature-based strategies to verify features in isolation have existed for years, they cannot address interactions between features. The problem with feature interactions is that they are typically unknown and may involve any subset of the features. Contrary, a family-based verification strategy captures feature interactions, but does not scale well when features evolve frequently. To the best of our knowledge, there currently exists no approach with focus on evolving features that combines both strategies and aims at eliminating their respective drawbacks. To fill this gap, we introduce Fefalution, a feature-family-based verification approach based on abstract contracts to verify evolving features and their interactions. Fefalution builds partial proofs for each evolving feature and then reuses the resulting partial proofs in verifying feature interactions, yielding a full verification of the complete software system. Moreover, to investigate whether a combination of both strategies is fruitful, we present the first empirical study for the verification of evolving features implemented by means of feature-oriented programming and by comparing Fefalution with another five family-based approaches varying in a set of optimizations. Our results indicate that partial proofs based on abstract contracts exhibit huge reuse potential, but also come with a substantial overhead for smaller evolution scenarios.

Pool-Based Realtime Algorithm Configuration: A Preselection Bandit Approach - El Mesaoudi-Paul, Adil; Weiß, Dimitri; Bengs, Viktor; Hüllermeier, Eyke; Tierney, Kevin (Learning and Intelligent Optimization. LION 2020.)

AuthCheck: Program-State Analysis for Access-Control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (Lecture Notes in Computer Science)

Schema Compliant Consistency Management via Triple Graph Grammars and Integer Linear Programming - Weidmann, Nils; Anjorin, Anthony (Proceedings of the 23rd International Conference on Fundamental Approaches to Software Engineering, FASE 2020)

Modeling and Analyzing Architectural Diversity of Open Platforms - Schwichtenberg, Bahar; Schwichtenberg, Simon; Küster, Jochen; Zimmermann, Olaf; Engels, Gregor (Advanced Information Systems Engineering)

Forward-Secure 0-RTT Goes Live: Implementation and Performance Analysis in QUIC - Dallmeier, Fynn; Drees, Jan P.; Gellert, Kai; Handirk, Tobias; Jager, Tibor; Klauke, Jonas; Nachtigall, Simon; Renzelmann, Timo; Wolf, Rudi (Cryptology and Network Security)
Modern cryptographic protocols, such as TLS 1.3 and QUIC, can send cryptographically protected data in “zero round-trip times (0-RTT)”, that is, without the need for a prior interactive handshake. Such protocols meet the demand for communication with minimal latency, but those currently deployed in practice achieve only rather weak security properties, as they may not achieve forward security for the first transmitted payload message and require additional countermeasures against replay attacks.Recently, 0-RTT protocols with full forward security and replay resilience have been proposed in the academic literature. These are based on puncturable encryption, which uses rather heavy building blocks, such as cryptographic pairings. Some constructions were claimed to have practical efficiency, but it is unclear how they compare concretely to protocols deployed in practice, and we currently do not have any benchmark results that new protocols can be compared with.We provide the first concrete performance analysis of a modern 0-RTT protocol with full forward security, by integrating the Bloom Filter Encryption scheme of Derler et al. (EUROCRYPT 2018) in the Chromium QUIC implementation and comparing it to Google’s original QUIC protocol. We find that for reasonable deployment parameters, the server CPU load increases approximately by a factor of eight and the memory consumption on the server increases significantly, but stays below 400 MB even for medium-scale deployments that handle up to 50K connections per day. The difference of the size of handshake messages is small enough that transmission time on the network is identical, and therefore not significant.We conclude that while current 0-RTT protocols with full forward security come with significant computational overhead, their use in practice is feasible, and may be used in applications where the increased CPU and memory load can be tolerated in exchange for full forward security and replay resilience on the cryptographic protocol level. Our results serve as a first benchmark that can be used to assess the efficiency of 0-RTT protocols potentially developed in the future.

Considering Context in Design Science Research: A Systematic Literature Review - zur Heiden, Philipp (Designing for Digital Transformation. Co-Creating Services with Citizens and Industry)

Parameterised Complexity of Model Checking and Satisfiability in Propositional Dependence Logic - Mahmood, Yasir; Meier, Arne (Lecture Notes in Computer Science)

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie M.; Furman, Susanne M.; Acar, Yasemin (HCI for Cybersecurity, Privacy and Trust)

A Value-Centered Approach for Unique and Novel Software Applications - Senft, Björn; Rittmeier, Florian; Fischer, Holger Gerhard; Oberthür, Simon (Design, User Experience, and Usability. Practice and Case Studies)

Exploiting Counterfactuals for Scalable Stochastic Optimization - Kuhlemann, Stefan; Sellmann, Meinolf; Tierney, Kevin (Lecture Notes in Computer Science)

Feature Selection for Analogy-Based Learning to Rank - Ahmadi Fahandar, Mohsen; Hüllermeier, Eyke (Discovery Science)

Analogy-Based Preference Learning with Kernels - Ahmadi Fahandar, Mohsen; Hüllermeier, Eyke (KI 2019: Advances in Artificial Intelligence)

Epistemic Uncertainty Sampling - Nguyen, Vu-Linh; Destercke, Sébastien; Hüllermeier, Eyke (Discovery Science)

How Good Is Good Enough? Establishing Quality Thresholds for the Automatic Text Analysis of Retro-Digitized Comics - Hartel, Rita; Dunst, Alexander (International Conference on Multimedia Modeling, MMM)

CoVeriTest: Cooperative Verifier-Based Testing - Beyer, Dirk; Jakobs, Marie-Christine (Fundamental Approaches to Software Engineering)

Parameterised Complexity of Abduction in Schaefer’s Framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Logical Foundations of Computer Science)

Practical, Anonymous, and Publicly Linkable Universally-Composable Reputation Systems - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (Topics in Cryptology - CT-RSA 2018 - The Cryptographers' Track at the RSA Conference 2018, Proceedings)

An Optimal Algorithm for Online Prize-Collecting Node-Weighted Steiner Forest - Markarian, Christine (International Workshop on Combinatorial Algorithms (IWOCA))
We study the Online Prize-collecting Node-weighted Steiner Forest problem (OPC-NWSF) in which we are given an undirected graph \(G=(V, E)\) with \(|V| = n\) and node-weight function \(w: V → \mathcal {R}^+\). A sequence of k pairs of nodes of G, each associated with a penalty, arrives online. OPC-NWSF asks to construct a subgraph H such that each pair \(\{s, t\}\) is either connected (there is a path between s and t in H) or its associated penalty is paid. The goal is to minimize the weight of H and the total penalties paid. The current best result for OPC-NWSF is a randomized \(\mathcal {O}(\log ^4 n)\)-competitive algorithm due to Hajiaghayi et al. (ICALP 2014). We improve this by proposing a randomized \(\mathcal {O}(\log n \log k)\)-competitive algorithm for OPC-NWSF, which is optimal up to constant factor since OPC-NWSF has a randomized lower bound of \(\varOmega (\log ^2 n)\) due to Korman [11]. Moreover, our result also implies an improvement for two special cases of OPC-NWSF, the Online Prize-collecting Node-weighted Steiner Tree problem (OPC-NWST) and the Online Node-weighted Steiner Forest problem (ONWSF). In OPC-NWST, there is a distinguished node which is one of the nodes in each pair. In ONWSF, all penalties are set to infinity. The currently best known results for OPC-NWST and ONWSF are a randomized \(\mathcal {O}(\log ^3 n)\)-competitive algorithm due to Hajiaghayi et al. (ICALP 2014) and a randomized \(\mathcal {O}(\log n \log ^2 k)\)-competitive algorithm due to Hajiaghayi et al. (FOCS 2013), respectively.

Ampehre: An Open Source Measurement Framework for Heterogeneous Compute Nodes - Lösch, Achim; Wiens, Alex; Platzner, Marco (Proceedings of the International Conference on Architecture of Computing Systems (ARCS))
Profiling applications on a heterogeneous compute node is challenging since the way to retrieve data from the resources and interpret them varies between resource types and manufacturers. This holds especially true for measuring the energy consumption. In this paper we present Ampehre, a novel open source measurement framework that allows developers to gather comparable measurements from heterogeneous compute nodes, e.g., nodes comprising CPU, GPU, and FPGA. We explain the architecture of Ampehre and detail the measurement process on the example of energy measurements on CPU and GPU. To characterize the probing effect, we quantitatively analyze the trade-off between the accuracy of measurements and the CPU load imposed by Ampehre. Based on this analysis, we are able to specify reasonable combinations of sampling periods for the different resource types of a compute node.

An FPGA/HMC-Based Accelerator for Resolution Proof Checking - Hansmeier, Tim; Platzner, Marco; Andrews, David (ARC 2018: Applied Reconfigurable Computing. Architectures, Tools, and Applications)
Modern Boolean satisfiability solvers can emit proofs of unsatisfiability. There is substantial interest in being able to verify such proofs and also in using them for further computations. In this paper, we present an FPGA accelerator for checking resolution proofs, a popular proof format. Our accelerator exploits parallelism at the low level by implementing the basic resolution step in hardware, and at the high level by instantiating a number of parallel modules for proof checking. Since proof checking involves highly irregular memory accesses, we employ Hybrid Memory Cube technology for accelerator memory. The results show that while the accelerator is scalable and achieves speedups for all benchmark proofs, performance improvements are currently limited by the overhead of transitioning the proof into the accelerator memory.

FastLane Is Opaque – a Case Study in Mechanized Proofs of Opacity - Schellhorn, Gerhard; Wedel, Monika; Travkin, Oleg; König, Jürgen; Wehrheim, Heike (Software Engineering and Formal Methods)

Information Flow Certificates - Töws, Manuel; Wehrheim, Heike (Theoretical Aspects of Computing – ICTAC 2018)
Information flow analysis investigates the flow of data in applications, checking in particular for flows from private sources to public sinks. Flow- and path-sensitive analyses are, however, often too costly to be performed every time a security-critical application is run. In this paper, we propose a variant of proof carrying code for information flow security. To this end, we develop information flow (IF) certificates which get attached to programs as well as a method for IF certificate validation. We prove soundness of our technique, i.e., show it to be tamper-free. The technique is implemented within the program analysis tool CPAchecker. Our experiments confirm that the use of certificates pays off for costly analysis runs.

Assist Users to Straightaway Suggest and Describe Experienced Problems - Senft, Björn; Fischer, Holger Gerhard; Oberthür, Simon; Patkar, Nitish (Design, User Experience, and Usability: Theory and Practice)

A Canvas Method to Foster Interdisciplinary Discussions on Digital Assistance Systems - Fischer, Holger Gerhard; Senft, Björn; Rittmeier, Florian; Sauer, Stefan (Design, User Experience, and Usability: Theory and Practice. Proceedings of the 20th International Conference on Human-Computer Interaktion (HCI International 2018))

Preference-Based Reinforcement Learning Using Dyad Ranking - Schäfer, Dirk; Hüllermeier, Eyke (Discovery Science)

A Dynamic Distributed Data Structure for Top-k and k-Select Queries - Feldkord, Björn; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Progress in Pattern Recognition, Image Analysis, Computer Vision, and Applications)

Scheduling Access to Shared Space in Multi-robot Systems - Khaluf, Yara; Markarian, Christine; Simoens, Pieter; Reina, Andreagiovanni (International Conference on Practical Applications of Agents and Multi-Agent Systems (PAAMS 2017))
Through this study, we introduce the idea of applying scheduling techniques to allocate spatial resources that are shared among multiple robots moving in a static environment and having temporal constraints on the arrival time to destinations. To illustrate this idea, we present an exemplified algorithm that plans and assigns a motion path to each robot. The considered problem is particularly challenging because: (i) the robots share the same environment and thus the planner must take into account overlapping paths which cannot happen at the same time; (ii) there are time deadlines thus the planner must deal with temporal constraints; (iii) new requests arrive without a priori knowledge thus the planner must be able to add new paths online and adjust old plans; (iv) the robot motion is subject to noise thus the planner must be reactive to adapt to online changes. We showcase the functioning of the proposed algorithm through a set of agent-based simulations.

Subtleties in Security Definitions for Predicate Encryption with Public Index - Blömer, Johannes; Liske, Gennadij (Proceedings of the International Conference of Mathematical Aspects of Computer and Information Sciences (MACIS))

Attribute-Based Encryption as a Service for Access Control in Large-Scale Organizations - Blömer, Johannes; Günther, Peter; Krummel, Volker; Löken, Nils (Foundations and Practice of Security)

Complexity of Single-Swap Heuristics for Metric Facility Location and Related Problems - Brauer, Sascha (Lecture Notes in Computer Science)
Metric facility location and K-means are well-known problems of combinatorial optimization. Both admit a fairly simple heuristic called single-swap, which adds, drops or swaps open facilities until it reaches a local optimum. For both problems, it is known that this algorithm produces a solution that is at most a constant factor worse than the respective global optimum. In this paper, we show that single-swap applied to the weighted metric uncapacitated facility location and weighted discrete K-means problem is tightly PLS-complete and hence has exponential worst-case running time.

Policy Dependent and Independent Information Flow Analyses - Töws, Manuel; Wehrheim, Heike (Formal Methods and Software Engineering - 19th International Conference on Formal Engineering Methods (ICFEM 2017))
Information Flow Analysis (IFA) aims at detecting illegal flows of information between program entities. “Legality” is therein specified in terms of various security policies. For the analysis, this opens up two possibilities: building generic, policy independent and building specific, policy dependent IFAs. While the former needs to track all dependencies between program entities, the latter allows for a reduced and thus more efficient analysis. In this paper, we start out by formally defining a policy independent information flow analysis. Next, we show how to specialize this IFA via policy specific variable tracking, and prove soundness of the specialization. We furthermore investigate refinement relationships between policies, allowing an IFA for one policy to be employed for its refinements. As policy refinement depends on concrete program entities, we additionally propose a precomputation of policy refinement conditions, enabling an efficient refinement check for concrete programs.

A Human-Centered Perspective on Software Quality: Acceptance Criteria for Work 4.0 - Fischer, Holger Gerhard; Engler, Michael; Sauer, Stefan (Design, User Experience, and Usability: Theory, Methodology, and Management)

Monitoring of Domain-Related Problems in Distributed Data Streams - Bemmann, Pascal; Biermeier, Felix; Bürmann, Jan; Kemper, Arne; Knollmann, Till; Knorr, Steffen; Kothe, Nils; Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm; Riechers, Sören; Schaefer, Johannes Sebastian; et al. (Structural Information and Communication Complexity)

Simulating Storage Policies for an Automated Grid-Based Warehouse System - Beckschäfer, Michaela; Malberg, Simon; Tierney, Kevin; Weskamp, Christoph (Lecture Notes in Computer Science)

Reducing the Verbosity of Imperative Model Refinements by Using General-Purpose Language Facilities - Gerking, Christopher; Schubert, David; Budde, Ingo (Theory and Practice of Model Transformation)

Population Coding: A New Design Paradigm for Embodied Distributed Systems - Hamann, Heiko; Valentini, Gabriele; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Collective Perception of Environmental Features in a Robot Swarm - Valentini, Gabriele; Brambilla, Davide; Hamann, Heiko; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Implementing Cryptographic Pairings on Accumulator Based Smart Card Architectures - Günther, Peter; Krummel, Volker (Mathematical Aspects of Computer and Information Sciences)

Theoretical Analysis of the k-Means Algorithm – A Survey - Blömer, Johannes; Lammersen, Christiane; Schmidt, Melanie; Sohler, Christian (Algorithm Engineering)

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Cross-Device Integration of Android Apps - Wolters, Dennis; Kirchhoff, Jonas; Gerth, Christian; Engels, Gregor (Service-Oriented Computing)
Integrating apps on mobile devices into applications running on other devices is usually difficult. For instance, using a messenger on a smartphone to share a text written on a desktop computer often ends up in a cumbersome solution to transfer the text, because many applications are not designed for such scenarios. In this paper, we present an approach enabling the integration of apps running on Android devices into applications running on other devices and even other platforms. This is achieved by specifying adapters for Android apps, which map their services to a platform-independent service interface. For this purpose, we have developed a domain-specific language to ease the specification of such mappings. Our approach is applicable without the need to modify the existing Android apps providing the service. We analyzed its feasibility by implementing our approach and by specifying mappings for several popular Android apps, e.g., phone book, camera, and file explorer.
Keywords: Cross-Device; Integration; Android; Adapter; DSL

Human-Centered Software Engineering as a Chance to Ensure Software Quality Within the Digitization of Human Workflows - Fischer, Holger Gerhard; Senft, Björn (Human-Centered and Error-Resilient Systems Development)

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Tightly-Secure Signatures from Chameleon Hash Functions - Blazy, Olivier; Kakvi, Saqib; Kiltz, Eike; Pan, Jiaxin (Lecture Notes in Computer Science)

AdIDoS – Adaptive and Intelligent Fully-Automatic Detection of Denial-of-Service Weaknesses in Web Services - Altmeier, Christian; Mainka, Christian; Somorovsky, Juraj; Schwenk, Jörg (Data Privacy Management, and Security Assurance - 10th International Workshop, DPM 2015, and 4th International Workshop, QASA 2015)

Practical Invalid Curve Attacks on TLS-ECDH - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Computer Security -- ESORICS 2015)

ECST – Extended Context-Free Straight-Line Tree Grammars - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Jeromin, Markus (Data Science - 30th British International Conference on Databases, BICOD 2015)

Understanding the Patient 2.0 - Geierhos, Michaela; Bäumer, Frederik S.; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context)

Understanding the Patient 2.0 - Geierhos, Michaela; Bäumer, Frederik S.; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context)

Swarm in a Fly Bottle: Feedback-Based Analysis of Self-organizing Temporary Lock-ins - Hamann, Heiko; Valentini, Gabriele (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Generating EAST-ADL Event Chains from Scenario-Based Requirements Specifications - Koch, Thorsten; Holtmann, Jörg; DeAntoni, Julien (Software Architecture)
Real-time software-intensive embedded systems complexity, as in the automotive domain, requires rigorous Requirements Engineering (RE) approaches. Scenario-based RE formalisms like Modal Sequence Diagrams (MSDs) enable an intuitive specication and the simulative validation of functional requirements. However, the dependencies between events occurring in different MSD scenarios are implicit so that it is difficult to find causes of requirements defects, if any. The automotive architecture description language EAST-ADL addresses this problem by relying on event chains, which make dependencies between events explicit. However, EAST-ADL event chains have a low abstraction level, and their relationship to functional requirements has seldom been investigated. Based on the EAST-ADL functional architecture, we propose to use its central notion of event to conciliate both approaches. We conceived an automatic transformation from the high abstraction level requirements specified in MSDs to the low abstraction level event chains.

Use Your Best Device! Enabling Device Changes at Runtime - Bokermann, Dennis; Gerth, Christian; Engels, Gregor (12th International Conference on Business Process Management (BPM 2014))

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Aggregation of Network Protocol Data Near Its Source - Fourné, Marcel; Stegemann, Kevin; Petersen, Dominique; Pohlmann, Norbert (Information and Communication Technology)

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Separating Regular Languages by Piecewise Testable and Unambiguous Languages - Place, Thomas; van Rooijen, Lorijn; Zeitoun, Marc (Mathematical Foundations of Computer Science 2013 - 38th International Symposium, (MFCS) 2013, Klosterneuburg, Austria, August 26-30, 2013)

Fast Multi-update Operations on Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas (Big Data - 29th British National Conference on Databases, BNCOD 2013,)

Evaluation of Rendering Algorithms Using Position-Dependent Scene Properties - Jähn, Claudius; Eikel, Benjamin; Fischer, Matthias; Petring, Ralf; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
In order to evaluate the efficiency of algorithms for real-time 3D rendering, different properties like rendering time, occluded triangles, or image quality, need to be investigated. Since these properties depend on the position of the camera, usually some camera path is chosen, along which the measurements are performed. As those measurements cover only a small part of the scene, this approach hardly allows drawing conclusions regarding the algorithm's properties at arbitrary positions in the scene. The presented method allows the systematic and position-independent evaluation of rendering algorithms. It uses an adaptive sampling approach to approximate the distribution of a property (like rendering time) for all positions in the scene. This approximation can be visualized to produce an intuitive impression of the algorithm's behavior or be statistically analyzed for objectively rating and comparing algorithms. We demonstrate our method by evaluating performance aspects of a known occlusion culling algorithm.

Real-Time 3D Rendering of Heterogeneous Scenes - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
Many virtual 3D scenes, especially those that are large, are not structured evenly. For such heterogeneous data, there is no single algorithm that is able to render every scene type at each position fast and with the same high image quality. For a small set of scenes, this situation can be improved if different rendering algorithms are manually assigned to particular parts of the scene by an experienced user. We introduce the Multi-Algorithm-Rendering method. It automatically deploys different rendering algorithms simultaneously for a broad range of scene types. The method divides the scene into subregions and measures the behavior of different algorithms for each region in a preprocessing step. During runtime, this data is utilized to compute an estimate for the quality and running time of the available rendering algorithms from the observer's point of view. By solving an optimizing problem, the image quality can be optimized by an assignment of algorithms to regions while keeping the frame rate almost constant.

Towards Swarm Calculus: Universal Properties of Swarm Performance and Collective Decisions - Hamann, Heiko; Engelbrecht, Andreas; Birattari, Mauro; Dorigo, Marco; Blum, Christian; Stuetzle, Thomas; Christensen, Anders Lyhne; Gross, Roderich (Swarm Intelligence: 8th International Conference, ANTS 2012)

Certifying RSA - Kakvi, Saqib; Kiltz, Eike; May, Alexander (Advances in Cryptology – ASIACRYPT 2012)

Optimal Security Proofs for Full Domain Hash, Revisited - Kakvi, Saqib; Kiltz, Eike (Advances in Cryptology – EUROCRYPT 2012)

Continuous Local Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Experimental Algorithms)

Local, Self-organizing Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems)